Maintien de l'ordre : étude des projets gouvernementaux 420-421-422-424 du 16 août 1962 - De Kock, Marc; Lallemand, Roger; Moureaux, Serge; Schellekens, Jacques; Calewaert, Willy (Bruxelles : Marc De Kock, 1962)
Archief André De Smet
Bibliotheek François Vercammen
Frans
Monografie
Keywords: stakingsrecht; regering; Ordehandhaving